Components of Perinatal Palliative Care: An Integrative Review - Laure Dombrecht; Kenneth Chambaere; Kim Beernaert; Ellen Roets; Mona De Vilder De Keyser; Gaëlle De Smet; Kristien Roelens; Filip Cools (MDPI AG, 2023)
When a severe diagnosis is made before or after birth, perinatal palliative care (PPC) can be provided to support the infant, parents and involved healthcare providers. An integrative and systematic overview of effectiveness and working components of existing PPC programs was needed. An integrative search was conducted in MEDLINE, Embase, CENTRAL, CINAHL, PsycInfo and Web of Science. Study designs examining the effect of PPC compared to regular care, and (empirical) articles describing the components of care included in existing PPC initiatives were included. Three independent authors reviewed titles, abstracts and full texts against eligibility criteria. PRISMA guidelines were followed; 21.893 records were identified; 69 publications met inclusion criteria. Twelve publications (17.4%) discussed the effect of a PPC program. Other publications concerned the description of PPC programs, most often by means of a program description (22/69; 31.9%), guidelines (14/769; 20.3%) or case study (10/69; 14.5%). Outcome measures envisioned four main target categories: care coordination, parents and family members, care for the fetus/neonate and healthcare providers. No trials exist to date. Analysis of working components revealed components related to changes directed to the policy of the hospital wards and components involving actual care being provided within the PPC program, directed to the fetus or infant, the family, involved healthcare providers or external actors. PPC is a growing research field where evidence consists mainly of descriptive studies and guidelines. The extensive list of possible PPC components can serve as a checklist for developing future initiatives worldwide. PPC includes several important actors: the fetus/infant and their family and included healthcare providers on both maternity and neonatal wards. This leads to a large variety of possible care components. However, while some studies show proof of concept, an evidence base to determine which components are actually effective is lacking.